Resurrection of Lamium ponticum (Lamiaceae) with a new subspecies, Lamium ponticum subsp. anatolicum, from Turkey - Celep, Ferhat; Karaer, Fergan; Duman, Hayri (Phytotaxa, 2021)
Lamium ponticum, known from central and eastern Black Sea region of Turkey, is an endemic species with white flowers. However, it was evaluated as a synonym of L. moschatum subsp. micranthum in the last taxonomic revision the genus. During our revisional studies on the genus, we concluded that L. ponticum is completely different from L. moschatum subsp. micranthum. In addition, we collected some specimens from western Black Sea region of Turkey with pink-rose colored flowers, pinkish-purplish inflorescence and calyx, and greenish-pinkish bracts with pinkish-white spots at base, that looks quite different from the typical L. ponticum. Therefore, in this paper, we resurrected L. ponticum and described a new subspecies from western Black Sea region of Turkey. IUCN red list category, notes on biogeography and ecology of the new subspecies are also given.